The underpricing of Brazilian IPOs and the adjustment to public and private information - Avelino, Ricardo (2013)
This paper examines the underwriters’ treatment of information throughout the IPO pricing process based on a sample of Brazilian companies that went public between 2004 and 2011. There is evidence that the offer price partially incorporates the information contained into the Bovespa index during the book-building period, reacting symmetrically to upward and downward movements. The first-day return, as a result, is predictable on the basis of this information. Positive private information disclosed during the book-building period is also partially incorporated into the offer price. Issues priced above the midpoint of the initial price range are associated with higher initial returns.